(3GdQbGHI Ydi OSJhQjI GdbhGfjf aj GdgfO (B: s (3OQGSI ebGQfI eY eUQ h GdhdGjGJ GdeJMOI GdCeQjcjI (B/ s - (3hLfGJ hgHg hQONGfs; (3jMji YHOGdYRjR GdLed s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2015)
(3JfGhd gPG GdHMK OQGSI ddQbGHI Ydi OSJhQjI GdbhGfjf ai GdgfO hGdebGQfI eY cd ef eUQ hGdhdGjGJ GdeJMOI GdGeQjcjI (B{u(32013(B} (3deG dgG ef GSdhH eJejR heJWhQ GfaQOJ Hg GdgfO ai QbGHJgG Ydi OSJhQjI GdbhGfjf(B. (3Ke JfGhd GdHMK OQGSI TGedI Yf OhQ GdeMceI GdYdjG GdgfOjI ai MeGjI GdMbhb GdGSGSjI ddehGWf GdgfOi hVeGf hUhd GdYOGdI Gdi LejY aFGJ GdeLJeY ef ZjQ GdbGOQjf Ydi GdhUhd Gdi GdeMceI GdYdjG HSHH GdLgd Gh GdabQ (B. (3ceG GTJed GdHMK Ydi GdbGA GdVhA Ydi GdOSJhQ GdgfOi hGdPi JYO GdQbGHI GdbVGFjI LRAG dG jJLRA efg GP gi HeKGHI GdHfjI GdGSGSjI dgPG GdOSJhQ(B. (3ceG GNJU GdOSJhQ GdeMceI GdYdjG HSdWGJ hGSYI JJjM dgG HSW QbGHJgG djS abW Ydi OSJhQjI GdbhGfjf Hd Ydi cd eG jJYdb HGdMbhb GdGSGSjI ddehGWfjf hMeGjJgG ef Gi GLQGAGJ JYSajI (B. (3HGdGVGaI Gdi OQGSI hGajI deaghe GdaGYdjI GdbVGFjI HeUWdMg GdLOjO GdPi Sei HGdJbGVi ef GLd GdUGdM GdYGe GdPi GMOK KhQI GLJeGYjI (B{u(32013(B} (3MjK hSYJ GdeMceI GdYdjG ef NdGd gPG GdfhY ef GdJbGVi ef eLGd GdMbhb GdGSGSjI Yf WQjb GdGfSdGN ef GLQGAGJ GdJbGVi GdJbdjOjI s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdYGe, (B2014s
(3HHdjhLQGajG(B: (3UaMGJ (B255-281s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdYGes; (3GdQbGHI GdSjGSjIs; (3GdhdGjGJ GdeJMOIs; (3MLjI GdGMcGe GdOSJhQjIs; (3GdaGYdjI GdbVGFjIs; (3GdeMceI GdOSJhQjI GdYdjGs; (3GdgfOs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdYGes